2002
DOI: 10.1128/jb.184.1.51-58.2002
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of thenfsAGene inEscherichia coliby SoxS

Abstract: In Escherichia coli, the response to oxidative stress due to elevated levels of superoxide is mediated, in part, by the soxRS regulon. One member of the soxRS regulon, nfsA, encodes the major oxygen-insensitive nitroreductase in Escherichia coli which catalyzes the reduction of nitroaromatic and nitroheterocyclic compounds by NADPH. In this study we investigate the regulation of nfsA in response to the superoxide generating compound paraquat. The transcription start site (TSS) of nfsA was located upstream of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…In addition, NADPH is the reductant or essential cofactor for several enzymes involved in protective and/or antioxidant activities, including glutathione reductase (GR), thioredoxin reductase, NADPH-dependent alkylhydroperoxidase and nitroreductase (Paterson et al, 2002;Imlay, 2008). Notably, several components of the soxRS and oxyR systems, such as glucose-6-phosphate dehydrogenase (G6PDH), ferredoxin-NADP(H) reductase (FPR), flavodoxin, GR and hydroperoxidase I are NADPHlinked enzymes or proteins.…”
Section: In Metabolic Terms Nadmentioning
confidence: 99%
“…In addition, NADPH is the reductant or essential cofactor for several enzymes involved in protective and/or antioxidant activities, including glutathione reductase (GR), thioredoxin reductase, NADPH-dependent alkylhydroperoxidase and nitroreductase (Paterson et al, 2002;Imlay, 2008). Notably, several components of the soxRS and oxyR systems, such as glucose-6-phosphate dehydrogenase (G6PDH), ferredoxin-NADP(H) reductase (FPR), flavodoxin, GR and hydroperoxidase I are NADPHlinked enzymes or proteins.…”
Section: In Metabolic Terms Nadmentioning
confidence: 99%
“…The protein homologous to NfrA in E. coli, NfsA, shares 37% amino acids with the NfrA protein of S. aureus. This protein is transcribed in an operon in which ybjC, a small ORF whose function is unknown, is located upstream of nfsA (19,30). In contrast to B. subtilis and E. coli, we found that the nfrA gene is transcribed monocistronically in S. aureus.…”
Section: Discussionmentioning
confidence: 65%
“…The 6His-SoxS purified protein, kindly provided by Paratek Pharmaceuticals, Boston, MA, or purified as described previously (36), was produced by cloning the soxS gene into the pET-15b expression plasmid and subsequently purifying the His-tagged protein. DNA containing the fumC, gnd, or znuC promoters was amplified by PCR using the primer pairs fumCF1/fumCR1, gndF/gndR, and znuC-proF/znuC-proR; the products were gel purified.…”
Section: Methodsmentioning
confidence: 99%